Pastoral Counseling Services For LGBT Congregations - Tony Tedjo; Rita Oktavia Gunarto; Yanto Sugiarto; Cindy Clarrisa Gabriela Febrian; Lemuel Anugerah Cristian (Budapest International Research and Critics University, 2021)
LGBT (Lesbian, Gay, Bisexual, and Transgender) people are currently becoming a topic of conversation in Indonesian society. The debate about LGBT is also viewed from various aspects of the life of the Indonesian people, especially from the moral and spiritual aspects. Some accept, and some also reject the existence of LGBT people. However, the church generally rejects their existence and excommunicates and punishes them. This attitude does not describe the church as a place to show love. LGBT people need a touch of love from the church with pastoral assistance. Through pastoral care provided by the church, LGBT people can be helped to experience recovery through a touch of Christ's love.